Intracellular synthesis of gold nanoparticles using alga tetraselmis kochinensis - Senapati, Satyajyoti; Syed, Asad; Moeez, Sana; Kumar, Ashutosh; Ahmad, Absar (Materials Letters, 2012)
The development of eco-friendly synthesis protocol for the synthesis of nanoscale materials of different compositions, shapes and sizes is an important area of research in the field of nanotechnology. In this paper, we report on the use of alga Tetraselmis kochinensis in the intracellular synthesis of gold nanoparticles of dimensions 5-35 nm. The particles are more concentrated upon the cell wall than on the cytoplasmic membrane, possibly due to reduction of the metal ions by enzymes present in the cell wall and cytoplasmic membrane. These intracellular nanoparticles may have applications in drug delivery, biomedical applications, catalysis, etc. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Algae; Biosynthesis; Nanoparticles; nanotechnology; Tetraselmis kochinensis

Isolation, purification and characterization of vinblastine and vincristine from endophytic fungus fusarium oxysporum isolated from catharanthus roseus - Kumar, Ashutosh; Patil, Deepak; Rajamohanan, Pattuparambil Ramanpillai; Ahmad, Absar (Plos One, 2013)
Endophytic fungi reside in a symbiotic fashion inside their host plants, mimic their chemistry and interestingly, produce the same natural products as their hosts and are thus being screened for the production of valuable compounds like taxol, camptothecin, podophyllotoxin, etc. Vinblastine and vincristine are excellent anti-cancer drugs but their current production using plants is non-abundant and expensive. In order to make these drugs readily available to the patients at affordable prices, we isolated the endophytic fungi from Catharanthus roseus plant and found a fungus AA-CRL-6 which produces vinblastine and vincristine in appreciable amounts. These drugs were purified by TLC and HPLC and characterized using UV-Vis spectroscopy, ESI-MS, MS/MS and H-1 NMR. One liter of culture filtrate yielded 76 mu g and 67 mu g of vinblastine and vincristine respectively. This endophytic fungal strain was identified as Fusarium oxysporum based upon its cultural and morphological characteristics and internal transcribed spacer (ITS) sequence analysis.

Identification of biomolecules involved in the biosynthesis of gold nanoparticles from living peanut seedlings - Raju, D.; Siddiqui, Ejaz Ahmad; Prasanth, S.; Khan, Bashir M.; Mehta, Urmil J.; Ahmad, Absar (Journal of Nanoscience and Nanotechnology, 2017)
In present work, we have fabricated gold nanoparticles by treating an aqueous solution of 10(-4) M HAuCl4 with the proteins extracted from roots of in vitro raised peanut seedlings and purified them by FPLC at room temperature. These proteins which tested positive for the reduction of 10(-4) M HAuCl4 were identified as Mannose glucose binding lectin and Ara h 8 allergen isoforms by ESI MS/MS. It is a well known fact that aromatic amino acids possess delocalized pi electrons in their ring structures, rendering them as the best electron donors which can transfer electrons and reduce the acceptor. These results suggest that the aromatic amino acids present in the proteins from the peanut seedlings are the primary biomolecules involved in the reduction of Au (III) to Au (0). We isolated different protein of molecular weight 16.4, 28.3 and 30 kDa involved in the formation of nanoparticles. The protein with molecular weight 16.4 kDa (allergens) yielded NPs of 25-60 nm whereas, the proteins with molecular weight 28.3 kDa and 30 kDa (lectins) yielded highly monodispersed NPs of 5-20 nm in size. The results clearly indicate that the size of nanoparticles can be controlled by different proteins.